2003
DOI: 10.1055/s-2003-42018
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Oxidative Changes During and Following the Western States Endurance Run

Abstract: Changes in immune and oxidative stress parameters were measured in ultramarathon runners competing in the 160-km Western States Endurance Run. Forty-five runners agreed to provide blood and saliva samples the morning before the race event, at the 90-km aid station, and 5 - 10 min post-race. Upper respiratory tract infection (URTI) during the two-week period post-race was assessed retrospectively by telephone interviews. Forty subjects completed 90-km (race time, 13.1 +/- 0.3 h), and 31 completed the 160-km rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 28 publications
2
36
1
3
Order By: Relevance
“…In that study, blood draws at 3000 m showed elevated plasma FRAP, suggesting that 3000 m would be adequate elevation to contribute to or exacerbate redox challenges, although the current findings suggest a more aggressive hypoxia is warranted. Other studies investigating ultra-marathon distances support an increase in plasma FRAP postexercise (Nieman et al, 2003;Quindry et al, 2008). Interestingly, current findings from our laboratory show that recovery from an identical exercise protocol, when performed in a hypoxic environment (5000 m) resulted in a decrease in plasma FRAP and TEAC compared with normoxic recovery (Ballmann et al, 2014).…”
Section: Plasma Antioxidant Capacity Biomarkerssupporting
confidence: 63%
“…In that study, blood draws at 3000 m showed elevated plasma FRAP, suggesting that 3000 m would be adequate elevation to contribute to or exacerbate redox challenges, although the current findings suggest a more aggressive hypoxia is warranted. Other studies investigating ultra-marathon distances support an increase in plasma FRAP postexercise (Nieman et al, 2003;Quindry et al, 2008). Interestingly, current findings from our laboratory show that recovery from an identical exercise protocol, when performed in a hypoxic environment (5000 m) resulted in a decrease in plasma FRAP and TEAC compared with normoxic recovery (Ballmann et al, 2014).…”
Section: Plasma Antioxidant Capacity Biomarkerssupporting
confidence: 63%
“…Its level was found to increase up to 100-fold, depending on intensity and duration of the endurance exercise [ 22 ]. According to the literature [ 22 , 47 ], the results at the end of the race in FR demonstrated an inflammatory response, stimulating the synthesis of IL-6-P (+5031%) as well as the excretion of IL-6-U (+83%) (see Fig 4A and 4B ), compared with Pre-Race values. Literature data suggest that plasma IL-6 response is related to the muscle glycogen content.…”
Section: Discussionmentioning
confidence: 54%
“…Von der HĂ€ufigkeit sind etwa 25-30% der LĂ€ufer nach einem Ultramarathon betroffen [112,116]. Im ‚Two Oceans Marathon' in Kapstadt, SĂŒdafrika, erlitten ĂŒber 30% der LĂ€ufer Infekte der oberen Luftwege wobei eher die schnellen LĂ€ufer betroffen waren [112].…”
Section: Bei Ultramarathons Wird Oft Ein Anstieg Des Kreatinins Und Eunclassified